Analiza statystyczna wybranych aspektów handlu zagranicznego II Rzeczypospolitej - Bębnowski, Damian (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2017)
Economic history is an interdisciplinary science, developing in the contact between history and economics, although this kind of studies often needs to refer to the achievements of other disciplines. In the economic history research it seems to be inspiring to use for example economic methods. The aim of this article is to present the results of statistical analysis which was about selected aspects of the Polish foreign trade in the interwar period. The data are obtained from ‘The Small Statistical Yearbook’ for years 1930–1939 and cover the period 1922–1939. The tests were conducted using statistical program ‘Gretl’ and the results were confronted with the selected literature. The analysis concerned the following dependences: import and export in Poland; import and domestic trade turnover in Poland; export and domestic trade turnover in Poland; Polish global import and import through the port of Gdynia; Polish global import and import through the port of Gdansk; Polish global export and export through the port of Gdynia; Polish global export and export through the port of Gdansk. There were also researched: the share of import through the ports of Gdynia and Gdansk in Polish global import, the share of export through the ports of Gdynia and Gdansk in Polish global export, the commodity composition of Polish import and export. For that purpose there were constructed the simple econometric models, based on the method, which is Pearson correlation coefficient. There were used basic descriptive statistics (arithmetic mean and median) and constructed the corresponding graphs and tables.